Mass transfer on MHD Free Convective Flow of Second Grade Fluid Past an Infinite Vertical Porous Plate - M. Kalpana, R. Bhuvana Vijaya (International Journal of Advanced Science and Technology, 2020)
We have seen the mass transfer on MHD free convective flow past an infinite vertical porous plate. We also considered time dependent permeability and oscillatory suction. The governing equations are solved by a regular perturbation method for small amplitude of the permeability. The solutions for main physical quantities have been derived discussed. The skin friction, the Nusselt number and Sherwood number are also obtained and their behavior computationally discussed.